Deskripsi Perilaku Kesehatan (Health Behavior) Dan Kualitas Hidup Lansia Suku Dayak Tomun Di Desa Sungai Buluh, Kab. Lamandau, Prov. Kalimantan Tengah - Yohana Pera; Desi Desi; Dennys Christovel Dese (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
AbstractBackground: The aging process makes the elderly experience physiological changes, susceptible to various diseases and physical deterioration. Elderly who do not have good health behavior will have a negative impact on their health. The negative impact of the aging process, for example a decline in physical condition, can reduce the level of independence of the elderly, lose their social role in society and mentally they feel inferior because they feel useless. The aging process has a negative impact on the quality of life of the elderly. Purpose: The purpose of this study was to examine the description of health behavior (Health Behavior) and the quality of life of the elderly Dayak Tomun tribe. Methods: This study uses qualitative methods with an approach through in-depth interviews in a semi-structured form. Respondents in this study were taken by purposive sampling amounting to 10 elderly people of the Dayak Tomun Tribe. Results: A supportive environment affects the quality of life of the elderly in the Dayak Tomun tribe, conditions and efforts to maintain / improve physical health, self-image, emotional color and spirituality of the elderly, social values in elderly interpersonal relationships, and elderly health behavior (aspects of knowledge, aspects of attitude and aspects of action). Conclusion: Health behavior of elderly respondents in the Dayak Tomun tribe is seen from the aspects of knowledge, aspects of attitude and aspects of good action. Meanwhile, the quality of life of the respondents is analyzed from 4 aspects, the elderly feel comfortable with their environment, the elderly are able to maintain their health condition, the elderly are able to accept themselves,achieve spiritual prosperity,and have good social relationships. Keywords: Elderly, Quality of Life and Health Behavior